International business and sustainable development - Verbeke, Alain; Strange, Roger (Emerald, 2013)
Sustainable development is arguably one of the prime issues in the world. It has social, ecological and economic dimensions, which makes it also a multi-faceted and complex problem. International Business scholars have stressed that the Multinational Enterprise should be considered the most important vehicle through which sustainable development occurs in developing countries. However, actual study of the topic remains fraught with theoretical and empirical caveats. This eighth volume in the Progress in international business research series includes new texts from a number of leading scholars and opinion leaders in the area. Contributors develop new levels of analysis (in particular global value chains or the partnership strategies of firms) that present promising areas for new theoretical and empirical insights. Whilst authors from leading international institutes are brought together in this volume, younger scholars with innovative ideas are also given room. The volume covers four dimensions of sustainable development, combining different scientific disciplines, levels of analysis and actor perspectives: 1. New trends and concepts in international business and sustainable development; 2. New corporate strategies for sustainable development; 3. New forms and levels of cooperation for sustainable development and 4. New public policies for sustainable development.
Keywords: Sustainable development.; International business enterprises.; Tulder, Rob van.; elektronické knihy; electronic books